2011
DOI: 10.1186/ar3271
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for ANA positivity in healthy persons

Abstract: IntroductionThe finding of antinuclear antibody (ANA) positivity in a healthy individual is usually of unknown significance and in most cases is benign. However, a subset of such individuals is at risk for development of autoimmune disease. We examined demographic and immunological features that are associated with ANA positivity in clinically healthy persons to develop insights into when this marker carries risk of progression to lupus.MethodsBiological samples from healthy individuals and patients with syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
116
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(131 citation statements)
references
References 28 publications
11
116
1
3
Order By: Relevance
“…16 Most of the ANA positive people don't developed an autoimmune disease and this is consisted with low prevalence of rheumatologic disorders (5-7%) despite the rate of ANA presence. 9 ANA positivity can be detected 20-30% at 1/40, 10% at 1/80 and 5% at 1/160 dilution in healthy people. 17 Li et al suggest that the persistence of the positive ANA may be a part of the component of the normal immune response.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…16 Most of the ANA positive people don't developed an autoimmune disease and this is consisted with low prevalence of rheumatologic disorders (5-7%) despite the rate of ANA presence. 9 ANA positivity can be detected 20-30% at 1/40, 10% at 1/80 and 5% at 1/160 dilution in healthy people. 17 Li et al suggest that the persistence of the positive ANA may be a part of the component of the normal immune response.…”
Section: Discussionmentioning
confidence: 98%
“…7 ANA positivity rate found in our female patients (77%) is consistent results with the knowledge of the autoimmune diseases are more frequent in women. 8,9 This predominance was researched by Leo and et al According to their study, the hormone profile, fetal microchimerism and some strategic genes which are on the sex chromosomes are playing role on this relationship. 10 As expected, the most of the positive ANA results were from rheumatology department (50%) in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model developed using selectively bred pedigreed rabbits remains a promising one for further genetic investigations. As is found in human sera (Li et al, 2011), some rabbits had detectable pre-immune antinuclear antibodies (ANA) by ELISA. ANA of sixteen of twenty-four rabbits in group 5, including four immunized with only MAP-8 backbone had an increased ELISA value (delta OD) above pre-immune of 1.0 or more optical density units after the third boost.…”
Section: Quantitative Real Time Pcrmentioning
confidence: 99%
“…Protein arrays containing microbial and autoantigens have been used to extend information on patients' serum profiles beyond the standard tests used in diagnosis (see for example, Robinson et al, 2002;Quintana et al, 2004;Li et al, 2005;Fattal et al 2010). Recently, Li et al, (2011) used protein microarrays to determine risk factors for ANA positivity in healthy persons and concluded that serum profiles of autoantibodies can potentially identify healthy individuals with potential to develop lupus and other autoimmune diseases. Their observations extended the widely quoted earlier observations by Arbuckle et al, (2003) that autoantibodies develop as much as ten years before the clinical onset of SLE.…”
Section: Rabbit Baffmentioning
confidence: 99%